4CPS-262 Place of clinical pharmacist in the management of patients undergoing bariatric surgery. (March 2019) - Rivet, A; Retur, N; Mendjel, A; Gugenheim, J; Dantin, T; Collomp, R
Abstract : Background: Obesity is a major national public health concern, with a prevalence of 15%. Among these patients, bariatric surgery procedures can be proposed, by sleeve gastrectomy or gastric bypass. Considering potential comorbidities of obesity (diabetes, arterial hypertension) many specialists are involved. Purpose: Our pharmacy department decided: to develop a pharmaceutical healthcare pathway in bariatric surgery for inpatients and outpatients: and to evaluate the relevance of medication reconciliation in this specific surgery. Material and methods: During the 3 month study period, the pharmacy department organised medication reconciliation in collaboration with the digestive surgery ward, and highlighted endpoints (including short-term stay at hospital) in the healthcare pathway of bariatric surgery where the pharmacist could be helpful. All patients undergoing bariatric surgery could be included for medication reconciliation. The number and type of discrepancies between admission medication and reconciled updated medication were reported, considering the particulars of medication management in surgery wards (such as switching oral by the IV route, usual peri- and post-operative management of anticoagulant, antihypertensive drugs). Results: The clinical pharmacist was integrated in initial information meetings for patients (including the organiser nurse, dietitians and a psychologist), which allowed him/her to answer questions from patients, collect their prescriptions and contact specialists, general practitioners and community pharmacists. The pharmacist received the surgical programme and planned admission reconciliation on day −1 before surgery. Forty-eight or 72 hours following surgery, the pharmacist explained the post-operative treatment and instructions with the patient (vitamin supplementation for life, crushing tablets during 45 days, contraindication for non-steroidal anti-inflammatory drugs and effervescent tablets). The community pharmacist received an informative leaflet and a mail was sent to the general practitioner and specialists detailing discharge medication reconciliation and proposing medication alternatives for non-crushing tablets. Concerning the relevance of medication reconciliation: 51 patients had reconciled medication, 33% showing at least one discrepancy (17/51). 32/47 total discrepancies were unintended with 21/32 of omitted medication and 10/32 dosage error. Conclusion: Integrating clinical pharmacy in the healthcare pathway of bariatric surgery is relevant, with a gain in care management both for inpatients and outpatients. This activity fits with national/regional indicators referring to the healthcare pathway for obesity. References and/or acknowledgements: Acknowledgements to the digestive surgery department of the Teaching Hospital of Nice. No conflict of interest.